Is mining fuelling long-run growth in Russia? Industry productivity growth trends since 1995 - Marcel P. Timmer; Ilya B. Voskoboynikov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
GDP per capita growth rates in Russia have been among the highest in the world since the mid?1990s. Previous growth accounting research suggests that this was mainly driven by multi-factor productivity (MFP) growth. In this paper we analyse for the first time the drivers of Russian growth for thirty-four industries over the period 1995 to 2008. We pay in particular attention to the construction of a proper measure of capital services, to use in place of the stock measures employed in previous research. Based on these new measures, we find that aggregate GDP growth is driven as much by capital input as by MFP growth. Mining and Retailing account for an increasing share of the inputs, but are weak in terms of MFP performance. In contrast, MFP growth was rapid in goods-producing industries, but the sector's GDP share declined. The major drivers of MFP growth were in the high-skilled services industries that were particularly underdeveloped in the Russian economy in the 1990s.
URN:NBN:fi:bof-201408072095
Keywords: O47; P28; L16; 330; industrial growth accounting; structural change; Russia